Asyptotic bounds for the solutions of functional and differentialfunctional equations with constant and linear delays - Bel’skii, D. V.; Pelyukh, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.929 We establish asymptotic bounds for the solutions of functional and differential-functional equations with linearly transformed arguments and constant delays.